FISHING GEAR AND FISH CATCH ASSESSMENT ALONG THE OTI RIVER AT AGBASAKOPE IN KRACHI EAST DISTRICT OF VOLTA REGION, GHANA - Akongyuure, D.N.; Ayiku, S.; Alhassan, E.H; Ampofo-Yeboah, A; Abarike, E.D; Abobi, S.M; Atindana, S. A. (UDS International Journal of Development, 2016)
Rivers are a great source of fish and contribute significantly to the fish consumed by many Ghanaians.Â However, catches from rivers have declined over the past few decades partly due to various illegal fishing activities. The study was conducted on the Oti RiverÂ atÂ Agbasakope in KrachiÂ East DistrictÂ inÂ the Volta Region of Ghana from December, 2013 to March, 2014 to assessÂ gearsÂ usedÂ andÂ fishÂ catches in order to provide technical information for sustainable exploitation of fish. Fishing gears were identified through personal observation. Fish catch data was obtained from randomly selected commercial fishermen once in a month. TheÂ resultsÂ revealedÂ thatÂ fishingÂ gearsÂ such as atidza net,Â beachÂ seine net,Â bambooÂ trapsÂ and gillnetsÂ wereÂ used.Â Gillnet was the most dominant fishing gear (47%) and the least used gear was atidza net (8%).Â The total average monthly fish catch was estimated as 10,027.9 kg during the period of study.Â Forty-six (46) fish species belonging to twelve (12) families were identified. Ten (10) species were caught from the family Cichlidae. Claroteidae was the most relatively abundant family (49.1%) with Chrysichthys auratus (20.1%) registering the highest percentage abundance in terms of number. MostÂ fishingÂ gearsÂ usedÂ byÂ the fishermen did not conform to those legally allowed by theÂ FisheriesÂ DirectorateÂ forÂ inland captureÂ fisheries. Ban on use of unauthorised fishing gears should be enforced to increase fish production on a sustainable basis from the River Oti. Keywords: Fish, Fishing gears, Catch, Fishermen and Oti River